PATRIMONIUL MUNICIPAL ÎN PREZENTARE VIRTUALĂ - BALTAG, Tatiana (BIBLIOPOLIS, 2020)
This article is about the city history reflected in the first blog of the Municipal Library B.P. Hasdeu – Chisinau, orasul meu. On the blog pages we can read the various information about our capital: generalities, history and present, personalities, images about the old and moderne Chisinau etc. The statistics tell us about the popularity of this resource, the comments – about it increasing subjects, themes